Bullying and associated factors among Brazilian adolescents: analysis of the National Adolescent School-based Health Survey (PeNSE 2012) - Deborah Carvalho Malta; Rogério Ruscitto do Prado; Antônio José Ribeiro Dias; Flavia Carvalho M. Mello; Marta Angelica Iossi Silva; Michelle Ralil da Costa; Waleska Teixeira Caiaffa (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To estimate the prevalence of bullying from the victim's perspective in Brazilian school children and to analyze its association with individual and family context variables. METHODS: An analysis of the data on 109,104 adolescents, obtained by the National Adolescent School-based Health Survey, held in schools in 2012, was carried out. An association model between bullying and explanatory variables was tested in different contexts: sociodemographic, risk behaviors, mental health and family context. Univariate and multivariate analyzes were performed, calculating the Odds Ratio and confidence intervals. RESULTS: The prevalence of bullying found in this study was of 7.2% (95%CI 6.6 - 7.8). A higher chance of bullying was found among male students (OR = 1.58; 95%CI 1.51 - 1.66), with an inverse relation between age and bullying, with the magnitude of risk among adolescents younger than 13 years of age being higher when compared to those with 16 years of age or more. Of individual risk behaviors, only being a smoker remained in the final model (OR = 1.11; 95%CI 1.01 - 1.23). Mental health variables associated with bullying were: feeling lonely (OR = 2.66; 95%CI 2.52 - 2.81), insomnia (OR = 1.92; 95%CI 1.80 - 2.05), not having friends (OR = 1.71; 95%CI 1.54 - 1.89), and, in the family context, those who skip class without telling their parents (OR = 1.13; 95%CI 1,07 - 1,19) and those who suffer physical abuse by family members (OR = 2.03; 95%CI 1.91 - 2.146). CONCLUSION: Bullying was associated to male students, younger, of black color, smokers, with mental health vulnerabilities and victims of domestic violence. This suggests the need for a holistic approach from education and health professionals, parents and the community in seeking measures for the prevention of bullying.